Effects of mastery learning strategy on senior school students' performance in mathematics in Osogbo, Nigeria - G. A. Akinpelu; M. F. Salman; S. A. Akinpelu; K. S. Ameen (Springer, 2024)
Abstract This study aimed to explore the effects of Mastery Learning Strategy (MLS) on senior school students' performance in Mathematics in Osogbo, Nigeria. The quasi-experimental study's goals were to investigate how MLS affected mathematics students' performance according to their gender and score levels. A purposive sampling technique was used to select two intact classes of 191 SS II students from two co-educational government senior secondary schools in Osogbo. The Geometric Constructions Test (GCT) which was made up of five theory questions adapted from WAEC mathematics past questions was used as the research instrument. GCT was revalidated by experts from the Department of Mathematics, University of Ilorin. The reliability index of 0.75 was obtained by test-retest method and Cronbach Alpha. Three research questions were raised from which three hypotheses were formulated. Data collected were analyzed using descriptive statistics, independent t-test and Analysis of Covariance (ANCOVA) at 0.05 level of significance. Findings revealed that MLS significantly improved students' performance (t(189) = 10.22, p < 0.05) while there was a significant difference in the performance of male and female students in favour of males (F(1, 94) = 33.06, p < 0.05). The strategy apparently helped to bridge the gap among students' scoring levels (F(2, 94) = 6.72, p < 0.05). The study found that, in comparison to the conventional method, MLS greatly enhanced students performance in mathematics. Hence, it was recommended that mathematics teachers should endeavour to adopt MLS in teaching Mathematics, especially in the perceived difficult topics.